The Non-linear Trajectory of Change in Play Profiles of Three Children in Psychodynamic Play Therapy - Halfon, Sibel; Çavdar, Alev; Orsucci, Franco; Schiepek, Gunter K.; Andreassi, Silvia; Giuliani, Alessandro; de Felice, Giulio (Frontiers in Psychology, 2016)
Aim: Even though there is substantial evidence that play based therapies produce significant change, the specific play processes in treatment remain unexamined. For that purpose, processes of change in long-term psychodynamic play therapy are assessed through a repeated systematic assessment of three children’s “Play Profiles”, which reflect patterns of organization among play variables that contribute to play activity in therapy, indicative of the children’s coping strategies, and an expression of their internal world. The main aims of the study are to investigate the kinds of Play Profiles expressed in treatment, and to test whether there is emergence of new and more adaptive Play Profiles using dynamic systems theory as a methodological framework. Methods and Procedures: Each session from the long-term psychodynamic treatment (mean number of sessions = 55) of three 6 year old good outcome cases presenting with Separation Anxiety were recorded, transcribed and coded using items from the Children's Play Therapy Instrument, created to assess the play activity of children in psychotherapy, generating discrete and measurable units of play activity arranged along a continuum of four play profiles: “Adaptive”, “Inhibited”, “Impulsive”, and “Disorganized”. The play profiles were clustered through K-means Algorithm, generating 7 discrete states characterizing the course of treatment and the transitions between these states were analyzed by Markov Transition Matrix, Recurrence Quantification Analysis (RQA) and odds ratios comparing the first and second halves of psychotherapy. Results: The Markov Transitions between the states scaled almost perfectly and also showed the ergodicity of the system meaning that the child can reach any state or shift to another one in play. The RQA and odds ratios showed two trends of change, first concerning the decrease in the use of “less adaptive” strategies, second regarding the reduction of play interruptions. Conclusions: The results support that these children express different psychic states in play, which can be captured through the lens of Play Profiles, and begin to modify less dysfunctional profiles over the course of treatment. The methodology employed showed the productivity of treating psychodynamic play therapy as a complex system, taking advantage of non-linear methods to study psychotherapeutic play activity.